Bilateral Asymmetric Traumatic Dislocation of the Hip Joint - Hee Gon Park; Hyung Suk Yi; Kyoo Hong Han (Journal of Trauma and Injury, 2018)
Traumatic hip joint dislocations account for 2–5% of total joint dislocations. Bilateral asymmetric hip joint dislocation with anteriorly and posteriorly dislocation is an even more rare case because it was according to G. Loupasis reported in 11 cases only since 1879. We want to report 2 cases of bilateral asymmetric hip joint dislocation with unilateral acatabulum fracture which happened in our hospital. Bilateral asymmetric dislocation of hip joint accompanied by unilateral fracture of acetabulum is a very rare case so statistical verification cannot be done. However, close examinations are required at early treatment and follow-up because the patterns of dislocation and fracture of hip joint are variable and an orthopedic emergent condition and several complications may occur at both hip joints.